Matthew - Osborne, Grant R.; Arnold, Clinton E. (Grand Rapids, Mich. : Zondervan, 2010)
In this volume, Grant Osborne offers pastors, students, and teachers a focused resource for reading the Gospel of Matthew. Through the use of graphic representations of translations, succinct summaries of main ideas, exegetical outlines, and other features, Osborne presents the Gospel of Matthew with precision and accuracy. Because of this series' focus on the textual structure of the scriptures, readers will better understand the literary elements of Matthew, comprehend the author's revolutionary goals, and ultimately discovering their vital claims upon the church today.
Series introduction -- Author's preface -- Abbreviations -- Introduction -- Select Bibliograpy -- Commentary -- Theology of Matthew -- Scripture Index -- Subject Index -- Author Index.
Includes bibliographical references (p. 49-56) and indexes.
Keywords: Bible. -- Commentaries